Performance analysis of water refrigerant heat pump with different configurations for high-temperature application - Wu, Di; Hu, Bin (Frontiers in Energy Research, 2023)
Water is a promising working fluid for high temperature heat pumps (HTHPs) with the advantages of being cheap, safe, stable, environmentally friendly, non-toxic and non-flammable. HTHPs using water as refrigerant not only can reduce greenhouse gas emissions in the industrial sectors by recovering waste heat, but also has no adverse effect on the environment if the refrigerant leaks. This article evaluates the safety, energy, and exergy performance of six designed HTHP configurations with water refrigerant by analysing the discharge superheat, power consumption, heating capacity, COP, and exergy efficiency -at different condensation and evaporation temperatures. The results indicated that water injection and intercooling can effectively decrease the discharge superheat to ensure safety performance. Among these systems, two-stage cycles can supply higher output temperatures and have better system performance than single-stage at high temperature lifts and large compression ratio conditions. The two-stage system with a flash tank (TS-FT) has the biggest heating capacity, the best COP, and the best exergy efficiency. With 80 ℃ evaporation temperature and 140 ℃ condensation temperature, the COP is 4.14 and the exergy efficiency is 70.9% for TS-FT. Compared with the singlestage ordinary system (SS-OS), the COP of TS-FT has an increment of 36.6%. The exergy efficiency of TS-FT is 19.8% higher than that of SS-OS. Considering the above theoretical analysis, TS-FT with the best safety, energy, and exergy performance is the optimal high temperature heat pump system with water refrigerant for high temperature applications.